PELATIHAN MITIGASI BENCANA DENGAN METODE KAMISHIBAI - Damayanti, S.; Purnawati, K.W.; Dewi, N.M.A.; Wedayanti, N.P.L.; Sulatri, N.L.P.A.; Bali, BPBD (Buletin Udayana Mengabdi; Vol 22 No 1 (2023): Buletin Udayana MengabdiDO - 10.24843/BUM.2023.v22.i01.p10, 2023)
Pering Village, Gianyar District is an area prone to earthquakes and tsunamis. The community service carried out with the theme "Disaster Mitigation Training with the kamishibai method" aims to train students and elementary school teachers in Pering Village to be responsive to earthquakes and tsunamis. The service which was carried out online through Webex media targeted SDN 5 Pering, Gianyar District, Bali. The disaster response training was carried out by telling a story entitled "I'm Not Afraid of the Earthquake and Tsunami" by Damayanti and illustrator Mirah (2021) using the kamishibai method. Then, the training was continued with socialization on disaster mitigation, and disaster response simulations by playing disaster response simulation videos. The results of this activity showed that the kamishibai method is an appropriate method to teach children about earthquake and tsunami disaster mitigation. Children easily understand how to deal with earthquakes and tsunamis after listening to fairy tales told through the kamishibai method. Dissemination of disaster mitigation and screening of simulation videos from the Regional Disaster Management Agency of the Province of Bali complement the knowledge and improve the skills of students and teachers in dealing with earthquake and tsunami disasters. It is hoped that this service can serve as an example for the community and government and private agencies who wish to improve the understanding and skills of children and teachers in dealing with disasters in schools. Keywords: disaster, earthquake, kamishibai, mitigation, storytelling, tsunami.